2018
DOI: 10.1016/j.ehj.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of primary PCI on diastolic dysfunction recovery in anterior wall STEMI – A non-invasive evaluation by echocardiography

Abstract: BackgroundIt is well established fact that acute coronary occlusion leads to diastolic dysfunction, followed by systolic dysfunction when myonecrosis occur. It is also proven that primary percutaneous coronary intervention (PPCI) is an excellent therapy for ST elevation myocardial infarction (STEMI) to improve outcomes. However there is a paucity of information on efficacy of PPCI in improving diastolic function. Evaluation of the role of PPCI in improving diastolic dysfunction is required.Methods61 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Compared to prior studies in which the follow-up period ranged from six months to two years, we only included patients with at least a three-year follow-up, which was the longest duration among previous studies. 1 , 6 , 25 , 28 Therefore, the results of our study may provide a powerful consensus that the role of the initial E/e’ ratio as a predictor for MACE or cardiac death does not end in the short term but is maintained for a long time.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Compared to prior studies in which the follow-up period ranged from six months to two years, we only included patients with at least a three-year follow-up, which was the longest duration among previous studies. 1 , 6 , 25 , 28 Therefore, the results of our study may provide a powerful consensus that the role of the initial E/e’ ratio as a predictor for MACE or cardiac death does not end in the short term but is maintained for a long time.…”
Section: Discussionmentioning
confidence: 69%
“…Certain factors have previously been reported as predictors of adverse clinical outcomes after STEMI, which have been related to decreased LVEF, deterioration of LVEF, and left anterior descending artery (LAD) as the culprit vessel. 28 , 29 Hospitalization due to adverse cardiac events may be associated with such issues. However, although higher percentages of decreased LVEF and LAD involvement were observed in the abnormal E/e’ ratio group, this result did not influence the overall MACEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, Subramaniyan et al, 30) showed that DD in STEMI patients was more likely to improve after primary PCI with shorter total ischemic times. This means more salvaged myocardium by early reperfusion and hence less myocardial necrosis.…”
Section: Discussionmentioning
confidence: 98%
“…LA function and deformation assessment in post-ST elevation myocardial infarction (STEMI) may provide insights into impaired LV mechanics and its hemodynamic recovery. LV diastolic dysfunction is a common feature in post-STEMI ( 10 ), and its impaired recovery ( 11 , 12 ) is an independent predictor of poor prognosis in post-STEMI. LA reservoir strain, a marker of LV diastolic dysfunction ( 5 , 13 ), has been proposed as a prognostic factor in post-STEMI; however, controversy regarding its dependency over and above LV dysfunction remains ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%